RENCANA PRODUKSI LABEL MENGGUNAKAN CHASE STRATEGY DI CV. FSA - Muhammad Fauzan Firdaus; Akhsani Nur Amalia; Farliana Sutartiah (Jurnal Industri dan Teknologi Samawa, 2024)
CV FSA is a company engaged in the printing sector. The main printing produced in this company is labels for various types of vegetables. A production activity needs to be planned well. In the process of producing labels, the production planning carried out by the company has not been effective because there are still labels that have not reached the production quantity, namely 33369 sweet mustard labels. This can reduce consumer satisfaction with the company. Therefore, there needs to be effective label production planning in the future. To estimate the number of future order requests, it can be done using the forecasting method. In this study, the forecasting method used is Additive Decomposition. This study aims to plan the production of sweet mustard labels from November 2023 to October 2024. The company only produces labels when there are orders from customers or make to order, so the production planning method that can be used is the chase strategy. The calculation results using the chase strategy method obtained the number of sweet mustard greens label production during regular hours in November 2023 to October 2024 were 9037, 9626, 9757, 9350, 9735, 8681, 9970, 9361, 10057, 8788, 9391, 9661 pcs with the largest number of workers needed being 5 people.